A PEM water electrolysis bipolar plate and preparation method thereof

By forming a cross-border pore structure and a multi-layer titanium structure on the stainless steel plate, the problems of water-electrolytic bipolar plates are solved, and a high-performance and low-cost water-electrolytic bipolar plate is realized.

CN115786956BActive Publication Date: 2025-02-11DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211538298.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-02-11
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

The existing water-electrolytic bipolar plates are prone to corrosion under high voltage and fluctuation states, and the conductivity of stainless steel plates is poor, resulting in high energy consumption and increased costs.

Method used

A stainless steel plate is used as a base, and a cross-border pore structure is provided, and a mixed titanium layer, a spherical dehydrogenated titanium powder layer and a functional coating are formed thereon. The flow field structure is formed by plasma spraying and mold printing technology.

Benefits of technology

It improves the stability, durability and conductivity of the bipolar plate, reduces costs, and at the same time enhances the bonding force between the titanium layer and the plate, improving the overall airtightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003976140140000011
    Figure HDA0003976140140000011
  • Figure HDA0003976140140000012
    Figure HDA0003976140140000012
  • Figure HDA0003976140140000021
    Figure HDA0003976140140000021
Patent Text Reader

Abstract

The present invention discloses a PEM water electrolysis bipolar plate and a preparation method, which belongs to the field of water electrolysis hydrogen production. The present invention uses a stainless steel plate as a substrate, and the substrate is provided with a perforated structure that is identical to the flow channel ridge structure and corresponds to the position. The upper and lower surfaces of the substrate are provided with a titanium layer, and the titanium layer fills the perforated structure and connects the upper and lower titanium layers. The surface of the titanium layer is provided with a spherical dehydrogenation titanium powder layer and a functional coating in sequence, and the functional coating forms the flow channel ridge, spoiler column and hydrogen and oxygen frame of the bipolar plate. The pore size of the spherical dehydrogenation titanium powder layer is 100nm-10μm; the titanium layer, the spherical dehydrogenation titanium powder layer and the functional coating all contain titanium powder. The present invention can improve the conductivity of the bipolar plate under the premise of using low-cost stainless steel plates, thereby improving the overall performance of the water electrolysis bipolar plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a PEM water electrolysis bipolar plate and a preparation method thereof, and belongs to the field of water electrolysis hydrogen production. Background Art

[0002] The bipolar plate is the core component of the water electrolysis cell, accounting for the vast majority of the weight and cost of the battery pack. The bipolar plate has a flow channel ridge, a spoiler zone containing spoiler columns, a hydrogen-oxygen frame, and a bridge zone. In addition, the bipolar plate also includes a flow channel groove and a hydrogen-oxygen cavity. The flow channel ridge, flow channel groove, spoiler zone, hydrogen-oxygen frame, and bridge zone form the flow field structure of the bipolar plate. The bipolar plate is not only required to have good electrical conductivity, thermal conductivity, and corrosion resistance, but also to have high mechanical strength and gas impermeability, so it has always been the focus and difficulty of development. The commonly used material for the bipolar plate of the solid polymer electrolyte water electrolysis cell is metal. Metal materials not only have good strength and toughness, but also have good mechanical processing performance, electrical conductivity, thermal conductivity, and density.

[0003] In the application process of water electrolysis, the operating conditions of bipolar plates are much more stringent than those of fuel cells. For example, under high pressure and fluctuating conditions, conventional stainless steel plates are difficult to meet the operating requirements and are prone to corrosion. In addition, the conductivity of stainless steel plates is poor, which will cause a lot of energy consumption during operation. Therefore, conventional water electrolysis materials generally use corrosion-resistant and conductive plates, such as titanium. Directly using pure titanium plates to prepare bipolar plates will increase the cost of water electrolysis. Therefore, it is very important to study how to use low-cost stainless steel metal materials to improve their corrosion resistance and conductivity. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a PEM water electrolysis bipolar plate with low cost and high performance and a batch preparation method.

[0005] The above technical purpose of the present invention is achieved through the following technical solutions:

[0006] The present invention provides a PEM water electrolysis bipolar plate, which uses a stainless steel plate as a substrate, and is provided with a through-strip hole structure corresponding to the position of the flow channel ridge and parallel to each other on the substrate, and a mixed titanium layer is provided on the upper and lower surfaces of the substrate, and the mixed titanium layer fills the through-strip hole structure and connects the upper and lower mixed titanium layer surfaces, and a spherical dehydrogenation titanium powder layer and a functional coating are sequentially provided on the surface of the mixed titanium layer, and the functional coating forms a flow field structure of the bipolar plate, and the mixed titanium layer and the functional coating both contain spherical atomized titanium powder.

[0007] Furthermore, the particle size of the spherical atomized titanium powder is 20-50 μm, the particle size of the spherical dehydrogenated titanium powder is 30-100 μm, and micropores are distributed in the spherical dehydrogenated titanium powder layer, and the pore size of the micropores is 100 nm-10 μm.

[0008] Furthermore, the thickness of the mixed titanium layer is 0.5-1 mm, the thickness of the spherical dehydrogenated titanium powder layer is 0.1-0.3 mm, the thickness of the functional coating is 0.2-0.5 mm, and the thickness of the stainless steel plate is 0.5-1 mm.

[0009] Furthermore, the stainless steel includes 304, 316 or 316L.

[0010] The present invention also provides a method for preparing a PEM water electrolysis bipolar plate, comprising the following steps:

[0011] (1) preparing a through-strip hole structure of a stainless steel plate so that the through-strip hole structure corresponds to the back position of the bipolar plate flow channel and is parallel to each other, and performing pretreatment;

[0012] (2) applying the mixed titanium layer slurry to the front and back surfaces of the plate treated in step (1) and filling the through-shaped holes;

[0013] (3) drying and hot pressing until the titanium-containing slurry on the stainless steel surface and in the pores reaches a compact state to obtain a metal composite plate;

[0014] (4) spraying spherical dehydrogenated titanium powder onto the surface of the metal composite plate by plasma spraying to form a spherical dehydrogenated titanium powder layer;

[0015] (5) Printing the functional layer slurry onto the spherical dehydrogenated titanium powder layer by mold printing to form a flow field structure. The flow field structure described here is a broad flow field structure, including but not limited to the flow field reaction area (flow channel ridges and flow to grooves), for example, also includes the inlet and outlet frames of the bipolar plate, the sealing frame (hydrogen and oxygen frame), the flow field distribution area, the bridge area, or the spoiler area. Those skilled in the art can form various structures by mold printing according to actual needs.

[0016] (6) Drying and removing the mold to obtain a water electrolysis bipolar plate.

[0017] Furthermore, the mixed titanium layer slurry and the functional layer slurry are both titanium-containing slurries; the titanium-containing slurry includes spherical atomized titanium powder with a particle size of 20-50 μm, a solvent, a binder and a plasticizer, and the mass ratio of the spherical atomized titanium powder to the solvent, the binder and the plasticizer is 60-80:15-35:3-4:1-2.

[0018] Furthermore, the solvent includes at least one of ethanol, toluene or methanol, the binder includes at least one of polyvinyl butyral resin or acrylic resin, and the plasticizer includes at least one of dioctyl phthalate, dibutyl phthalate or propylene glycol phthalate polyester.

[0019] Furthermore, the conditions of the plasma spraying are: plasma enthalpy is 22-50 MJ / kg; spraying speed is 600-1000 mm / s; and spraying temperature is 150-200°C.

[0020] Furthermore, in the steps (3) and (6), the drying temperature is 100-150°C, and the drying time is 3-5 min; the hot pressing conditions are: pressure 0.1-4 MPa, holding time 120-180 s, and hot pressing temperature 60-150°C.

[0021] Furthermore, the pretreatment method in step (1) includes: grinding the stainless steel plate formed with the through-strip hole structure step by step, and then polishing and rinsing with clean water.

[0022] Furthermore, the surface of the stainless steel plate is polished step by step using sandpaper with a mesh number of 500 to 1200.

[0023] Furthermore, the surface of the stainless steel plate is polished in stages using sandpaper with mesh sizes of 500, 700, 900, and 1200, respectively.

[0024] Furthermore, in step (5), the titanium-containing slurry is printed onto the spherical dehydrogenated titanium powder layer by mold printing to form a functional coating having flow field structures such as the flow channel ridges, spoiler columns and hydrogen and oxygen frames of the bipolar plate, including: placing a plurality of thin tubes in parallel and at intervals on the surface of the spherical dehydrogenated titanium powder layer, so that one end of the thin tubes corresponds to the hydrogen and oxygen cavity of the bipolar plate, and the other end of the thin tubes corresponds to the spoiler area, and then placing the mold parallel to the front surface of the spherical dehydrogenated titanium powder layer, and printing the functional mixed slurry on the spherical dehydrogenated titanium powder layer along the shape of the mold to form a functional coating having the flow channel ridges, spoiler columns and hydrogen and oxygen frames of the bipolar plate.

[0025] Furthermore, the mold includes a hollow area and a closed area, the hollow area is for the functional mixed slurry to pass through to form the flow channel ridge, spoiler column and hydrogen and oxygen frame of the bipolar plate, and the closed area is for shielding the bipolar plate where the flow field structure does not need to be formed to form the flow channel grooves of the bipolar plate, the spoiler area except the spoiler column and the processing area for the subsequent hydrogen and oxygen cavity; the capillary is placed at a position corresponding to the hollow area. After printing is completed, the capillary is removed to form a fine pore structure, i.e., a bridge area, between the hydrogen and oxygen cavity and the spoiler area for material to enter and exit.

[0026] The present invention is further configured as follows: the preparation method of the present invention can be used for batch preparation of water electrolysis bipolar plates, including milling, grinding and polishing, slurry stirring, slurry filling, drying and hot pressing, plasma spraying, composite plate cutting, mold placement, slurry printing, drying and demolding, etc. The connection between each step is completed by a mechanical arm or a mechanical transmission module to complete the automatic operation; the capillary is placed accurately by a mechanical module, and the position error is 0.01 to 0.05 mm.

[0027] The present invention is further configured such that the composite plate is cut by a laser cutting machine to cut out the hydrogen and oxygen cavities of the bipolar plate.

[0028] The present invention has the following beneficial effects:

[0029] 1. High stability: The present invention performs cross-penetration on the surface of stainless steel, generates parallel and consistent cross-penetration strip holes at the corresponding bipolar plate flow channel ridge position, then covers the upper and lower sides of the stainless steel plate and fills the cross-penetration strip holes with titanium-containing slurry, and then performs drying and hot pressing. The unstable stainless steel is completely covered with the titanium-containing slurry, and a layer of titanium-containing slurry is scraped on the upper and lower sides of the stainless steel. After hot pressing, the titanium-containing slurry on both the surface and the inside of the stainless steel is compacted to ensure air tightness. The mixed titanium layer on the front and back sides of the stainless steel plate is connected by the cross-penetration strip holes on the plate to form an integral structure, so the titanium layer will not fall off easily. In addition, by using a press to apply pressure, the membrane-based bonding force on the front and back sides of the stainless steel plate is stronger, the durability is better, and the stability of the water electrolysis bipolar plate is greatly improved.

[0030] 2. High durability and conductivity: The back of the bipolar plate is in direct contact with the membrane electrode, and the membrane electrode is the core of the reaction, with a changing potential and a local acidic system. Therefore, the side of the metal plate in contact with the membrane electrode will directly contact the high potential and the acidic aqueous solution. By using the structure of the present invention, the corresponding position of the back of the bipolar plate is pure titanium, and titanium has excellent conductivity and stability, while the functional coating is used in the lower layer of pure titanium to provide higher strength and durability. Compared with the traditional single-structure bipolar plate, it not only retains high conductivity, but also makes the bipolar plate have higher durability.

[0031] 3. High performance: The present invention uses low-cost stainless steel as the substrate, and then uses titanium-containing slurry to physically modify the stainless steel substrate, that is, first lay a solid substrate layer foundation, and add a small amount of titanium material to make the substrate have lower resistance; then use ion spraying to evenly spray a spherical dehydrogenated titanium powder layer on the mixed titanium layer. The powdered titanium material is combined with a detailed ion spraying method to form a uniform pure titanium thin layer, which further saves costs and effectively improves the overall conductivity and durability. Finally, a functional coating containing titanium powder is used to prepare a flow field structure to meet performance requirements. While achieving the goal, it also achieves the goal of saving cost; in summary, compared with the bipolar plate with a pure titanium structure of a certain thickness, the present invention is prepared by doping titanium powder or forming a thin layer of titanium powder, and the purpose requirements are divided in a targeted manner. For example, titanium powder doping is used purposefully in substrate modification and flow field structure because the main purpose of these two steps is to form a structurally stable substrate and a flow field structure. Therefore, these two steps can relatively dope a small amount of titanium to achieve the goal of saving costs, and a thin layer of pure titanium is densely sprayed between the substrate layer and the flow field structure in order to ensure the overall performance.

[0032] 4. Simple preparation process: The present invention forms an integral titanium layer (spherical dehydrogenated titanium powder layer and functional coating) on ​​the substrate of the stainless steel plate by plasma spraying and printing, which can improve the conductivity and corrosion resistance of the bipolar plate while realizing the integrated preparation of the water electrolysis bipolar plate. In the traditional preparation process, the partition plate and the hydrogen and oxygen frame need to be machined separately, and then glued together to realize the assembly and forming of the bipolar plate. In this way, due to the presence of glue, the bonding strength and integrity will affect the resistance and air tightness of the bipolar plate. The present invention directly prepares the structure of the bipolar plate on the stainless steel plate. After the titanium layer is plasma sprayed, the hydrogen and oxygen cavity structure is formed through a mold in the subsequent printing process. No additional gluing, welding and other processes are required to achieve the sealing of the bipolar plate, which greatly improves the production efficiency and saves costs.

[0033] 5. The present invention first sprays a layer of spherical dehydrogenated titanium powder on the surface of the composite plate by plasma spraying. Since high temperature is generated during the plasma spraying process, the particles on the surface of the plate will be melted. At this time, spraying titanium particles can effectively make the titanium particles penetrate into the surface of the plate, and the titanium particles are more densely distributed, thereby increasing the bonding force between the plate and the titanium layer. Then, a functional coating is printed on the surface of the spherical dehydrogenated titanium powder layer. Due to the presence of micropores in the spherical dehydrogenated titanium powder layer and the influence of printing pressure, the mutual penetration of titanium particles between the two titanium layers can be effectively enhanced, thereby improving the bonding force between the two, that is, effectively increasing the bonding force between the overall titanium layer and the plate. The present invention is equivalent to batch preparation of the titanium layer, thereby having a stronger bonding force and improving the conductivity and durability of the bipolar plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a schematic diagram of the overall structure of the customized mold in this embodiment.

[0035] Figure 2 Schematic diagram of the placement of the capillary when printing the functional coating.

[0036] Figure 3 Schematic diagram of the bipolar plate after printing with a customized mold.

[0037] Figure 4 This is a cross-sectional view of the bipolar plate spoiler area after printing with a customized mold.

[0038] Figure 5 Schematic diagram of the structure of the metal composite plate.

[0039] Figure 6 It is a schematic diagram of the batch preparation process of the present invention.

[0040] In the figure: 1. hollow area; 2. closed area; 3. capillary; 4. hydrogen-oxygen cavity; 5. flow channel groove; 6. flow channel ridge; 7. turbulent area; 8. material inlet and outlet holes; 9. functional coating; 10. spherical dehydrogenated titanium powder layer; 11. metal composite plate; 5-1. mixed titanium layer; 5-2. composite layer; 5-2-1. titanium slurry; 5-2-2. stainless steel plate; 6-1. milling and piercing; 6-2. grinding and polishing; 6-3. slurry stirring; 6-4. slurry filling; 6-5. drying and hot pressing; 6-6. plasma spraying; 6-7. composite plate cutting; 6-8. mold placement; 6-9. slurry printing; 6-10. drying and demolding. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0042] Embodiment 1:

[0043] Preparation of titanium-containing slurry: Weigh 60 g of spherical atomized titanium powder with a particle size of 20 μm (the spherical atomized titanium powder obtained by atomization treatment can be prepared by a general method in the art), 35 g of anhydrous ethanol, 4 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir evenly with a mechanical stirrer for later use.

[0044] Cut a piece of 304 stainless steel plate with a thickness of 0.5mm and an area of ​​20cmx10cm, and use a milling machine to pierce the plate body to form a number of parallel arranged pierced strip hole structures on the plate body. The piercing position corresponds to the position of the subsequent bipolar plate channel ridge 6 and is parallel to the bipolar plate channel ridge 6; then use 200-500 mesh sandpaper to grind and polish step by step, and then put the stainless steel plate 5-2-2 into acetone solution for ultrasonic cleaning 3 times, each time for 10 minutes, then rinse with ultrapure water, and then take out and blow dry.

[0045] The titanium-containing slurry is evenly scraped onto the front and back surfaces of the stainless steel plate 5-2-2 to form a mixed titanium layer 5-1 and fill the through-strip hole structure, and then placed in a 100°C oven for heat treatment for 5 minutes. After the time is up, the plate is taken out and placed on a hot press platform for hot pressing. The hot press platform pressure is 4Mpa, the holding time is 120s, and the hot pressing temperature is 150°C to obtain a metal composite plate body 11. The thickness of the mixed titanium layer 5-1 on both the front and back surfaces of the metal composite plate body 11 is 1mm. Then, put it on the plasma spraying platform, set the spraying machine conditions to plasma enthalpy of 22MJ / kg; spray speed of 600mm / s; spray temperature of 150°C, spray spherical dehydrogenated titanium powder with a particle size of 30μm (spherical dehydrogenated titanium powder obtained by dehydrogenation treatment can be prepared by a general method in the art) onto the surface of the metal composite plate 11 to obtain a spherical dehydrogenated titanium powder layer 10, and the spherical dehydrogenated titanium powder layer 10 has holes with a diameter of 100nm. Then, multiple capillaries 3 are placed in parallel and at intervals on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent area 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the titanium-containing slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the shape of the mold to form a functional coating 9, and finally a laser cutting machine is used to cut and form the hydrogen and oxygen cavity 4. The customized mold includes a hollow area 1 and a closed area 2. The hollow area 1 is for the titanium-containing slurry to pass through to form the required bipolar plate structure, that is, it corresponds to the bipolar plate flow channel ridge 6, spoiler column and hydrogen and oxygen frame (the hydrogen and oxygen frame is the peripheral frame of the hydrogen and oxygen cavity 4 and the sealant wire groove part of the bipolar plate that needs to be sealed), and the closed area 2 is to block the bipolar plate where no structure needs to be formed, that is, it corresponds to the bipolar plate flow channel groove 5, the spoiler area 7 except the spoiler column and the hydrogen and oxygen cavity 4 (for hydrogen and oxygen to enter and exit the bipolar plate respectively), etc., as shown Figure 1 and 3 As shown; the above-mentioned thin tube 3 corresponds to the hollow area 1 of the customized mold in position, so that the titanium-containing slurry can pass through the printing, and a material inlet and outlet hole 8 is formed between the hydrogen and oxygen cavity and the turbulent area under printing, which can allow hydrogen to enter from the hydrogen and oxygen cavity and enter the flow field after passing through the thin hole, and flow out from the flow field to the hydrogen and oxygen cavity at the outlet end, that is, the bridge area, as shown Figure 2 and 4 As shown, the thickness of the customized mold is 0.3 mm, and then it is placed in a 100° C. oven for heat treatment for 5 minutes. After the time is up, the mold is removed, and the thin tube 3 is taken out. Finally, a laser cutting machine is used to cut to form a hydrogen and oxygen cavity 4 to prepare a water electrolysis bipolar plate.

[0046] The process of the present invention is simple. The surface of the stainless steel plate 5-2-2 is pierced and titanium slurry is injected. After testing, the contact resistance of the prepared bipolar plate is 0.77mΩ·cm2 , the corrosion current density is 4.15μA / cm 2 Moreover, the back of the bipolar plate corresponding to the stainless steel penetration position, that is, the corresponding position of the back of the entire water electrolysis bipolar plate, is made of titanium slurry 5-2-1, and the stack directly corresponds to the membrane electrode. Therefore, the prepared water electrolysis bipolar plate has higher performance and conductivity.

[0047] Embodiment 2:

[0048] Preparation of titanium-containing slurry: weigh 70 g of spherical atomized titanium powder with a particle size of 35 μm, 20 g of anhydrous ethanol, 3.5 g of polyvinyl butyral resin, and 1.5 g of dioctyl phthalate in a beaker, and stir evenly with a mechanical stirrer for later use.

[0049] Cut a piece of 304 stainless steel plate with a thickness of 0.75mm and an area of ​​20cmx10cm, and use a milling machine to pierce the plate body to form a number of parallel arranged piercing strip hole structures on the plate body. The piercing position corresponds to the position of the subsequent bipolar plate flow channel ridge 6 and is parallel to the bipolar plate chute ridge 6; then use 200-500 mesh sandpaper to grind and polish step by step, and then put the stainless steel plate 5-2-2 into acetone solution for ultrasonic cleaning 3 times, each time for 10 minutes, then rinse with ultrapure water, and then take out and blow dry.

[0050] The titanium-containing slurry is evenly scraped onto the front and back surfaces of the stainless steel plate 5-2-2 to form a mixed titanium layer 5-1 and fill the through-strip hole structure, and then placed in a 100°C oven for heat treatment for 5 minutes. After the time is up, the plate is taken out and placed on a hot press platform for hot pressing. The hot press platform pressure is 4Mpa, the holding time is 150s, and the hot pressing temperature is 100°C to obtain a metal composite plate body 11. The thickness of the mixed titanium layer 5-1 on both the front and back surfaces of the metal composite plate body 11 is 1mm. Then, it is placed on the plasma spraying platform, and the spraying machine conditions are set to plasma enthalpy of 36MJ / kg; spraying speed of 800mm / s; spraying temperature of 175°C, and spherical dehydrogenated titanium powder with a particle size of 60μm is sprayed onto the surface of the metal composite plate 11 to obtain a spherical dehydrogenated titanium powder layer 10, and then a plurality of capillaries 3 are placed in parallel and spaced on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent zone 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold plate is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the titanium-containing slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the mold shape to form a functional coating 9, and finally a laser cutter is used to cut to form the hydrogen and oxygen cavity 4. The customized mold structure is the same as in Example 1, and the thickness of the customized mold is 0.4 mm. It is then placed in a 125°C oven for heat treatment for 4 minutes. After the time is up, the mold is removed and the capillary 3 is removed to prepare a water electrolysis bipolar plate.

[0051] The test shows that the water electrolysis bipolar plate prepared in this embodiment has high performance, and its contact resistance and corrosion current density are 0.73mΩ·cm 2 and 4.23μA / cm 2 .

[0052] Embodiment 3:

[0053] Preparation of titanium-containing slurry: weigh 80 g of spherical atomized titanium powder with a particle size of 50 μm, 15 g of anhydrous ethanol, 3 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir them evenly with a mechanical stirrer for later use.

[0054] Cut a piece of 316 stainless steel plate with a thickness of 1mm and an area of ​​20cmx10cm, and use a milling machine to pierce the plate body to form a number of parallel arranged piercing strip hole structures on the plate body. The piercing position corresponds to the position of the subsequent bipolar plate flow channel 6 and is parallel to the bipolar plate chute spine 6; then use 200-500 mesh sandpaper to grind and polish step by step, and then put the stainless steel plate 5-2-2 into acetone solution for ultrasonic cleaning 3 times, each time for 10 minutes, then rinse with ultrapure water, and then take out and blow dry.

[0055] The titanium-containing slurry is evenly scraped onto the front and back surfaces of the stainless steel plate 5-2-2 to form a mixed titanium layer 5-1 and fill the through-strip hole structure, and then placed in a 100°C oven for heat treatment for 5 minutes. After the time is up, the plate is taken out and placed on a hot press platform for hot pressing. The hot press platform pressure is 4Mpa, the holding time is 180s, and the hot pressing temperature is 60°C. A metal composite plate body 11 is obtained, and the thickness of the mixed titanium layer 5-1 on both the front and back surfaces of the metal composite plate body 11 is 1mm. Then, it is placed on the plasma spraying platform, and the spraying machine conditions are set to plasma enthalpy of 50MJ / kg; spraying speed of 1000mm / s; spraying temperature of 200°C, and spherical dehydrogenated titanium powder with a particle size of 100μm is sprayed on the surface of the metal composite plate body 11 to obtain a spherical dehydrogenated titanium powder layer 10, and then a plurality of capillaries 3 are placed in parallel and spaced on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the spoiler area 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold plate is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the titanium-containing slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the mold shape to form a functional coating 9, and finally a laser cutter is used to cut to form the hydrogen and oxygen cavity 4. The customized mold structure is the same as in Example 1, and the thickness of the customized mold is 0.5 mm. It is then placed in a 150°C oven for heat treatment for 3 minutes. After the time is up, the mold is removed and the capillary 3 is removed to prepare a water electrolysis bipolar plate.

[0056] The test shows that the water electrolysis bipolar plate prepared in this embodiment has high performance, and its contact resistance and corrosion current density are 0.71 mΩ·cm 2 and 4.14μA / cm 2 .

[0057] Comparative Example 1 (no penetration, direct stainless steel plate 5-2-2 spraying)

[0058] Preparation of titanium-containing slurry: weigh 60 g of spherical atomized titanium powder with a particle size of 20 μm, 35 g of anhydrous ethanol, 4 g of polyvinyl butyral resin, and 1 g of dioctyl phthalate in a beaker, and stir them evenly with a mechanical stirrer for later use.

[0059] A piece of 304 stainless steel plate with a thickness of 0.5 mm and an area of ​​20 cm x 10 cm was cut and polished step by step using 200-500 mesh sandpaper. The plate was then ultrasonically cleaned in an acetone solution for 3 times, each time for 10 minutes. After cleaning, it was rinsed with ultrapure water and then taken out and blown dry.

[0060] The cleaned stainless steel plate 5-2-2 is placed on the plasma spraying platform, and the spraying machine conditions are set to a plasma enthalpy of 22MJ / kg; a spraying speed of 600mm / s; and a spraying temperature of 150°C. Spherical dehydrogenated titanium powder with a particle size of 30μm is sprayed onto the stainless steel surface to form a spherical dehydrogenated titanium powder layer 10. Subsequently, a plurality of capillaries 3 are placed in parallel on the surface of the spherical dehydrogenated titanium powder layer 10, and one end of the capillaries 3 corresponds to the hydrogen and oxygen cavity 4 of the bipolar plate, and the other end of the capillaries 3 corresponds to the turbulent flow zone 7, as shown in FIG. Figure 2 and 4 As shown, the customized mold plate is then placed parallel to the front surface of the spherical dehydrogenated titanium powder layer 10, and the slurry is printed on the spherical dehydrogenated titanium powder layer 10 along the mold shape to form a functional coating 9; the structure of the customized mold is the same as that of Example 1, and the thickness of the customized mold is 0.3 mm. It is then placed in an oven at 100°C for heat treatment for 5 minutes. After the time is up, the mold is removed and the capillary 3 is taken out to prepare a water electrolysis bipolar plate.

[0061] In this comparative example, a spherical dehydrogenated titanium powder layer 10 is directly plasma sprayed on the stainless steel surface, and then a titanium-containing slurry is printed to form a titanium protective layer on the stainless steel surface. Therefore, its contact resistance is small, which is 0.12 mΩ·cm higher than that of Example 1. 2 It may be that after the stainless steel is penetrated and filled with titanium-containing slurry, Example 1 is subjected to hot pressing treatment, which makes the titanium layer on its surface more compact. In addition, since Example 1 is penetrated, it is equivalent to the penetration position, that is, the back position of the bipolar plate flow field, which is full titanium material, so it has a lower contact resistance. However, this comparative example only forms a titanium-containing functional coating on the stainless steel surface, resulting in a contact resistance higher than that of Example 1 by 0.12 mΩ·cm. 2 result.

[0062] Table 1 Test results

[0063] Serial number <![CDATA[Contact resistance mΩ·cm 2 > <![CDATA[Corrosion current density μA / cm 2 > Example 1 0.55 2.15 Example 2 0.53 2.23 Example 3 0.51 2.14 Comparative Example 1 0.67 3.25

[0064] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A PEM water electrolysis bipolar plate, characterized in that: A stainless steel plate is used as a substrate, and the substrate is provided with a through-strip hole structure corresponding to the ridge position of the flow channel and parallel to each other. The upper and lower surfaces of the substrate are provided with a mixed titanium layer, and the mixed titanium layer fills the through-strip hole structure and connects the upper and lower mixed titanium layer surfaces. A spherical dehydrogenated titanium powder layer and a functional coating are sequentially provided on the surface of the mixed titanium layer. The functional coating forms a flow field structure of the bipolar plate, and the mixed titanium layer and the functional coating both contain spherical atomized titanium powder.

2. A PEM water electrolysis bipolar plate according to claim 1, characterized in that: The particle size of the spherical atomized titanium powder is 20-50 μm, and the particle size of the spherical dehydrogenated titanium powder is 30-100 μm; micropores are distributed in the spherical dehydrogenated titanium powder layer, and the pore size of the micropores is 100 nm-10 μm.

3. A PEM water electrolysis bipolar plate according to claim 1, characterized in that: The thickness of the mixed titanium layer is 0.5-1 mm, the thickness of the spherical dehydrogenated titanium powder layer is 0.1-0.3 mm, the thickness of the functional coating is 0.2-0.5 mm, and the thickness of the stainless steel plate is 0.5-1 mm.

4. A method for preparing a PEM water electrolysis bipolar plate, characterized in that: The preparation method comprises the following steps: (1) preparing a through-strip hole structure of a stainless steel plate so that the through-strip hole structure corresponds to the back position of the bipolar plate flow channel and is parallel to each other, and performing pretreatment; (2) applying the mixed titanium layer slurry to the front and back surfaces of the plate treated in step (1) and filling the through-shaped holes; (3) drying and hot pressing to obtain a metal composite plate; (4) spraying spherical dehydrogenated titanium powder onto the surface of the metal composite plate by plasma spraying to form a spherical dehydrogenated titanium powder layer; (5) printing the functional layer slurry onto the spherical dehydrogenated titanium powder layer by mold printing to form a flow field structure; (6) drying and removing the mold to obtain a water electrolysis bipolar plate; The mixed titanium layer slurry and the functional layer slurry are both titanium-containing slurries, which include spherical atomized titanium powder with a particle size of 20-50 μm, a solvent, a binder and a plasticizer. The mass ratio of the spherical atomized titanium powder to the solvent, the binder and the plasticizer is 60-80:15-35:3-4:1-2.

5. The method for preparing a PEM water electrolysis bipolar plate according to claim 4, characterized in that: The solvent includes at least one of ethanol, toluene or methanol, the binder includes at least one of polyvinyl butyral resin or acrylic resin, and the plasticizer includes at least one of dioctyl phthalate, dibutyl phthalate or propylene glycol phthalate polyester.

6. The method for preparing a PEM water electrolysis bipolar plate according to claim 4, characterized in that: The conditions of the plasma spraying are: plasma enthalpy of 22-50 MJ / kg; spraying speed of 600-1000 mm / s; and spraying temperature of 150-200°C.

7. The method for preparing a PEM water electrolysis bipolar plate according to claim 4, characterized in that: The drying temperature in step (3) and step (6) is 100-150°C; the hot pressing conditions are: pressure 0.1-4Mpa, holding time 120-180s, and hot pressing temperature 60-150°C.

8. The method for preparing a PEM water electrolysis bipolar plate according to claim 4, characterized in that: The pretreatment method in step (1) comprises: grinding the stainless steel plate with the through-strip hole structure step by step, and then polishing and rinsing with clean water.

9. The method for preparing a PEM water electrolysis bipolar plate according to claim 4, characterized in that: The connection between each step is completed through a robotic arm or mechanical transmission module to achieve automated operation.

Citation Information

Patent Citations

  • Fuel cell stainless steel bipolar plate preparation and surface modification method

    CN110289428A

  • Fuel cell gas diffusion layer with novel structure and preparation method

    CN114744215A